GDP‐fucose transporter SLC35C1: a potential regulatory role in cytosolic GDP‐fucose and fucosylated glycan synthesis - Edyta Skurska; Mariusz Olczak (FEBS Open Bio)
Glycosylation occurs mainly in the Golgi apparatus, whereas the synthesis of nucleotide sugars occurs in the cytoplasm or nucleus. GDP‐fucose in mammalian cells could be produced via de novo and salvage pathways in the cytoplasm; the first one is responsible for about 90% of GDP‐fucose in the total pool of this nucleotide sugar in the cell. SLC35C1 (C1) is the primary transporter of GDP‐fucose to the Golgi apparatus. In the absence of this transporter, it was proposed that nucleotide sugar could still reach the Golgi apparatus via a SLC35C2, the homologue of SLC35C1. However, simultaneous inactivation of the two transporters did not influence GDP‐fucose transport across the Golgi apparatus membranes after external fucose supplementation. In this study, we combined the inactivation of SLC35C1 and enzymes of the GDP‐fucose biosynthesis pathways (FCSK, GMDS and TSTA3) to study the impact of double inactivation on the production of nucleotide sugar and fucosylated glycans. We found that a lack of SLC35C1 changed the level of enzymes of both de novo and salvage pathways. Upon fucose supplementation, stimulation of the salvage pathway was remarkably high in the absence of the TSTA3 protein, and the concentration of GDP‐fucose increased to millimolar values. In this work, we discovered that simultaneous deficiency of the SLC35C1 protein and TSTA3 enzyme increased GDP‐fucose production via the salvage pathway to an even higher level. Finally, we found that nucleotide sugar still accessed the Golgi apparatus and had differential effects on N‐ and O‐glycans.